The Use of Brainlab Navigation in Le Fort III Osteotomy. Issue 3 (May 2015) - Wood, Jeyhan S.; Purzycki, Adam; Thompson, Jim; David, Lisa R.; Argenta, Louis C.
<x xml:space="preserve">Abstract</x> Abstract Le Fort III osteotomy is commonly used in the surgical correction of midface hypoplasia, specifically in patients with syndromic craniosynostosis. These osteotomies can be associated with significant complications, which are often the result of incomplete or inaccurate osteotomies. Brainlab, a technology first developed for neurosurgery, has been applied to numerous surgical subspecialties. The aim of this study was to report our initial experience using the Brainlab VectorVision2 and Brainlab Curve (Brainlab, Westchester, IL) as an intraoperative guidance system for osteotomy placement during Le Fort III advancement. Three pediatric patients with syndromic craniosynostosis and midface hypoplasia scheduled to undergo Le Fort III advancement were scanned preoperatively with 0.6-mm computed tomography cuts, which were then uploaded to the Brainlab system. All surgeries commenced with rigid fixation of the Brainlab registration device to the patient's skull. The navigation system was used intraoperatively to accurately determine osteotomy sites and trajectories. External distractors were placed without complication. Mean length of surgery was 331 minutes, and mean estimated blood loss was 500 mL. No transfusion was required with a mean postoperative hemoglobin of 8.3 g/dL. The application of Brainlab technology to Le Fort III advancement proved useful in establishing precise osteotomy lines and trajectories. Looking forward, this technology could be applied to a minimal dissection technique in order to avoid extensive blood loss. Further study would be needed to determine possible benefits such as reduced complications or operative time when using an intraoperative navigation system for image-guided osteotomy placement during Le Fort III advancement.